Assessment of grading in newly-diagnosed glioma using 18F-fluorothymidine PET/CT - Ferdová, Eva; Ferda, Jiří; Baxa, Jan; Tupý, Radek; Mraček, Jan; Topolčan, Ondřej; Hes, Ondrej (Anticancer research, 2015)
AIM: To evaluate the proliferation activity in gliomas using 18F-fluorothymidine (18F-FLT)-positron emission tomography/computed tomography (PET/CT). PATIENTS AND METHODS: Samples of 26 tumors were analyzed (mean age=51.6; range=26-72 years; 16 males, 10 females). All examinations were performed using a PET/CT scanner equipped with lutetium oxyorthosilicate (LSO) detectors. All data were acquired with a delay of 15 min, following intravenous application of 18F-FLT (dosed 2 MBq/kg of body weight). The PET/CT contained CT after intravenous application of iodinated contrast agent and high-resolution brain PET acquired during 15 min in one position. PET/CT was performed before confirmation of the histological diagnosis and the level of 18F-FLT accumulation was compared to the grading of the tumor evaluated using immunohistochemistry staining of Ki-67. Samples were obtained by stereotactic biopsy (5×) or surgical resection (21×). RESULTS: Five tumors of grade IV, 7 tumors of grade III and 14 tumors of grade II were found. Pre-bioptical discrimination between high-grade and low-grade tumors reached accuracy 92.3% (24/26), sensitivity 92.3% (12/13) and specificity 92.9 (13/14). The mean maximum standardized uptake value (SUVmax) in high-grade tumors was 2.23, significantly different from low-grade tumors (mean SUVmax 0.61, T=7.803, p<0.0001). CONCLUSION: 18F-FLT-PET/CT enables to estimate the proliferation activity of glioma before biopsy.
Keywords: dospělí; Tomography, X-Ray Computed; pozitronová emisní tomografie; Multimodal Imaging; Humans; lidé středního věku; Middle Aged; PET/CT; fluorothymidine; Positron-Emission Tomography; fluorodeoxyglukosa F18; multimodální zobrazování; Fluorodeoxyglucose F18; mužské pohlaví; Adult; Brain tumors; proliferation activity; ženské pohlaví; Brain Neoplasms; nádory mozku; lidé; tumor grading; počítačová rentgenová tomografie; Aged; senioři; Male; Female